2012
DOI: 10.4236/jmmce.2012.119082
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Response Optimization of Three-Body Abrasive Wear Behaviour of Graphite Filled Carbon-Epoxy ComPosites Using Grey-Based Taguchi Approach

Abstract: The three-body abrasive wear behaviour of carbon fabric reinforced epoxy (C-E) composites has been evaluated by the addition of graphite (G) particles as a secondary reinforcement. Three-body abrasive wear test were conducted using dry sand rubber wheel abrasion tester as per ASTM G-65 with three process parameters load, abrading distance and filler content. To assess the abrasive wear behaviour of particulate filled C-E composites satisfying multiple performance measure, grey-based Taguchi approach has been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Taguchi method was applied for wear behavior of polymer matrix composites [57,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]. It can be seen that the grit size was pre-dominant parameter on the wear properties [109][110][111][112][113][114], followed by the load [12].…”
Section: Taguchi Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Taguchi method was applied for wear behavior of polymer matrix composites [57,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]. It can be seen that the grit size was pre-dominant parameter on the wear properties [109][110][111][112][113][114], followed by the load [12].…”
Section: Taguchi Designmentioning
confidence: 99%
“…It was revealed that the effect of variables (PV) factor and filler content [116][117][118][119][120][121][122] was more pronounced on the sliding wear of glass-vinyl ester composites. Tribological property of 60 wt% carbon fabrics containing up to 5 wt% alumina nano particles fabricated by mixing method associated with compression molding method was investigated using a Taguchi method by taking into accounts of nano addition, load, speed and grit size [113].…”
Section: Taguchi Designmentioning
confidence: 99%
“…It was found that several fillers in epoxy coating considerably decrease its wear [1]. Threebody abrasive wear characteristic of carbon-epoxy composite with and without silicon carbide filler was studied by Subbaya et al [2]. They have used Taguchi L27 orthogonal array, by using grey relational analysis, carried out the experiments and optimized the process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties are augmented more with fibers when compared with other reinforcements. There are many researchers who investigated the potential of the fiber reinforcements like carbon fibers, glass fibers, and basalt fibers on the epoxy matrix in benefitting the tribological properties [9][10][11][12]. Suresha et al [9] have discussed that the carbon fiber composites are having better wear resistance than the glass fiber based epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…Suresha et al [9] have discussed that the carbon fiber composites are having better wear resistance than the glass fiber based epoxy composites. Subbayya et al [10] have applied L 27 design and proved that the abrading distance, filler content and the load when considered individually have a higher significance and higher percentage of contribution than considered in combination. Ramesh and Suresha [13] have incorporated Taguchi, ANOVA and discussed that filler loading has the more influence than that of the normal load, under two-body abrasion also compared the relation between the sliding and abrasion wear.…”
Section: Introductionmentioning
confidence: 99%